Latent hidden factor model for Malaysian consumer price index - Nurulkamal Masseran; Siti Norsalsabila Ahmad Farouk; Nur-Firyal, R.; Mahayaudin M. Mansor (Penerbit Universiti Kebangsaan Malaysia, 2024)
The consumer price index (CPI) is one of the significant indicators that can be used to track the inflation rate of a country and assess changes in the cost of living. Generally, the CPI measures the change in the average price of goods and services used by households. The increase in inflation can have a negative socioeconomic effects and the changes in the CPI value needs to be monitored to ensure that the country does not experience a serious inflation rate. In this work, exploratory factor analysis (EFA) was employed to interpret the importance of each variable in the CPI and determine how the latent factors influence the CPI structure in Malaysia for the period of 2003–2022. The findings showed that there are two main latent factors that can be formed. Factor 1 can be classified as ‘Household Expenditures and Lifestyle Choices’ and consists of six variables, namely, ‘alcoholic beverages and tobacco’, ‘housing, water, electricity, gas, and other fuels’, ‘decoration, hardware, and household maintenance’, ‘health’, ‘recreational and cultural services’, and ‘education’. In contrast, Factor 2 can be classified as ‘Daily Necessities and Lifestyle Convenience’ which consists of six variables, namely, ‘food and non-alcoholic beverages’, ‘clothing and shoes’, ‘transportation’, ‘communication’, ‘restaurants and hotels’, and ‘various goods and services’. In addition, the results of our analysis showed that Factor 1 is more dominant in influencing the CPI structure in Malaysia.